Pork quality after electrical or carbon dioxide stunning at slaughter - Marcon, Adila V.; Caldara, Fabiana R.; Oliveira, Geyssane F. de [UNESP]; Goncalves, Liliane M. P.; Garcia, Rodrigo G.; Paz, Ibiara C. L. A. [UNESP]; Crone, Carla; Marcon, Alex (Elsevier B.V., 2019)
A total of 172 pigs were randomly allocated to two stunning treatments: carbon dioxide (CO2) and electrical stunning at a commercial abattoir. The Longissimus lumborum (LL) muscle was used to evaluate the effects of stunning methods on pork quality and financial losses of carcasses and viscera condemnation was also determined following by sanitary inspection. There was no effect due to stunning method on quality parameters (P > .137) of pH 24, drip or thaw loss, lipid oxidation, myofibrillar fragmentation index, shear force or PSE / DFD meat incidence. The LL muscle of the electrically stunned pigs had a higher L * value (P < .05), higher cooking loss (P < .001) and lower pH 45 (P < .05) compared to those stunned with CO2. CO2 stunned pigs had fewer carcasses condemned due to fractures / lesions (P < .05), hepatic and renal congestion (P < .05). CO2 stunning can be beneficial from an economic point of view because it has reduced losses through condemnation at the slaughterhouse.
Keywords: Fracture; Viscera; Congestion; Condemnation; Carcass